The determining factors that influencing health care management among Jabatan Kesihatan Negeri Selangor employees / Nur Alyaa Zafirah Kamarzaman - Kamarzaman, Nur Alyaa Zafirah (2016)
This study provides the important contribution to the Malaysia that want to have good healthy lifestyle and have knowledge how to manage their health care in understanding of individual behaviour, sociocultural and health education as preferences. The purpose of this study is to investigate on how employees in Jabatan Kesihatan Negeri Selangor manage their health care. A sample size of 130 respondents is drawn at Jabatan Kesihatan Negeri Selangor included Malay, Indian and Chinese respondents. The result has been analysed to see their significant and the relationship between three variables individual behaviour, sociocultural and health education with dependent variable, health care management on multiple regression analysis. The data analysis showed that half of the employees are aware about health and have a significant positive effect with the evidence from coefficient result